Flow-Diverter Stenting of Intracavernous Internal Carotid Artery Mycotic Aneurysm - Imamura, Hirotoshi; Sakai, Nobuyuki; Alexander, Michael J. (Journal of Stroke and Cerebrovascular Diseases, 2019)
This is the first reported case in which a mycotic aneurysm refractory to the first medical treatment was treated with a Pipeline embolization device (PED), and the first case of a mycotic aneurysm from Brucella treated by endovascular therapy. A 35-year-old man presented with left eye pain and ptosis, and fever for 2 weeks. Before symptom onset, he visited Vietnam where he developed a flu-like illness; however, antibiotics were ineffective. We suspected Brucella as the most likely infectious etiology for the patient's intracavernous aneurysm. Since the aneurysm did not reduce in size following 2 weeks of antibiotic therapy, we placed a PED in the left internal carotid artery. Follow-up angiogram 4 months later showed no residual aneurysm, and cranial nerve palsies had completely resolved. From the results of this case, it appears that flow diverter stenting may be a safe and effective treatment of mycotic aneurysms of the cavernous segment of ICA.